Long Squash—an Asian Vegetable Emerging in Florida - Guodong Liu; Yuncong Li; David Dinkins; Bonnie Wells; Qingren Wang; Yuqi Cui (EDIS)
Long squash is an annual, vigorous, and herbaceous crop that was brought to the Americas by Paleoindian populations from Asia before the arrival of Columbus. This 4-page fact sheet provides an overview of this plant as well as recommendations for individuals in Florida who are interested in growing it. Written by Guodong Liu, Yuncong Li, David Dinkins, Bonnie Wells, Qingren Wang, and Yuqi Cui, and published by the UF Department of Horticultural Sciences, December 2015.